Organisational commitment and job satisfaction as antecedents of organisational citizenship behaviour at the water utility company in Gauteng - Motaung, Thembi Laura (My University, 2016)
Organisations need employees who are willing to go beyond the requirements of the job to contribute to the organisation’s effectiveness. An evolving trend in the organisational behaviour literature indicates that job satisfaction (JS) and organisational commitment (OC) are attitudes that have a major impact on organisational outcomes such as productivity, job performance, turnover intentions and organisational citizenship behaviour (OCB). Although the relationship between the aforementioned constructs is considered important, there is a paucity of research about the relationship between these constructs in the context of the water utility company. The primary objective of this study was to investigate the impact of organisational commitment and job satisfaction on organisational citizenship behaviour at the water utility company in Gauteng. A quantitative research approach and a survey-based descriptive research method were used to achieve the primary objective. A structured questionnaire was issued to 400 randomly sampled respondents. Furthermore, means and factor analysis were performed to determine the level of job satisfaction, organisational commitment and organisational citizenship behaviour of employees and to establish the underlying factors of the constructs respectively. Additionally, a correlation analysis was conducted to establish the strength and direction of the relationship between the factors. Finally, a regression analysis was performed to confirm the predictive relationship between factors. The findings of this study showed a positive correlation between affective commitment, indebted obligation and moral imperative; JS and OCB; and no predictive relationship was observed between continuance commitment and OCB. Based on the findings, it was recommended that JS should be improved through mechanisms such as job-fit, job enrichment and career advancement. Furthermore, performance-related pay and mentorship programmes should be introduced to improve employees’ organisational commitment. Finally, recognition should be given to employees to encourage them to maintain their willingness to display citizenship behaviours.
M. Tech. (Business Administration, Faculty of Management Sciences), Vaal University of Technology
Keywords: Organizational behaviour; Job satisfaction; Organisational commitment; Water utility company; Performance related pay; 658.31423